Democracy and taxation - Pavlos Balamatsias (Kiel Institute for the World Economy (IfW), 2017)
In this paper, the author argues that democracies tend to positively affect the size and composition of tax revenues. His argument is based on the hypothesis that democracies can increase direct taxation, such as income taxes and capital taxes, due to increased compliance of taxpayers and also because there is a diffusion of tax measures between neighboring democratic/autocratic countries. The main theoretical hypothesis is then tested on a dataset that consists of 74 countries over the period 1993-2012. His main explanatory variable will be a dichotomous measure of democracy; but he alters his analysis from previous research by assuming that democracy or autocracy is not an exogenous variable. Instead the author follows the theory of Huntington (The third wave: Democratization in the late twentieth century (Vol. 4), 1991) and the methodology of Acemoglu et al. (Democracy does cause growth, 2014) about regional democratization waves. According to this theory, democratizations occur in regional waves; consequently diffusion of demand or discontent for a political system is easier to happen in neighboring countries due to socio-political and historical similarities. This measure shows him that demand or discontent for a given political system in a geographical area, can in turn influence the power of a country's political regime and subsequently that regime's effect on taxation. The author then uses a two stage least square (2SLS) fixed effects to test our hypothesis. The empirical findings suggest that regional waves of democratization have a positive and statistically significant correlation with democracy, and in turn democracy also has a positive effect on direct taxation as well as the ratio of direct to indirect taxation in the countries of his sample. This result remains the same when several robustness tests are used. Finally when examining the long-run effect of regional waves, the author does not find any evidence of a significant relationship between regional waves of democratization and a country's own regime; however democracy still has a positive effect on direct taxes and tax ratio.
Keywords: P16; H2; 330; democracy; political development; regional democratization waves; taxation